2017
DOI: 10.1021/acsnano.6b08008
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly of Hierarchical DNA Nanotube Architectures with Well-Defined Geometries

Abstract: An essential motif for the assembly of biological materials such as actin at the scale of hundreds of nanometers and beyond is a network of one-dimensional fibers with well-defined geometry. Here, we demonstrate the programmed organization of DNA filaments into micron-scale architectures where component filaments are oriented at preprogrammed angles. We assemble L-, T-, and Y-shaped DNA origami junctions that nucleate two or three micron length DNA nanotubes at high yields. The angles between the nanotubes mir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 64 publications
(109 reference statements)
1
48
0
1
Order By: Relevance
“…One of the typical successful examples would be DNA nanotechnology such as DNA origami in which various structures can be logically nanoarchitected through specific baseparing and programmed DNA sequences [200][201][202]. Schulman and co-workers demonstrated hierarchic self-assembly of DNA nanotubes in micrometre scale from DNA strands with programmed sequences [203]. Even though the assembled structures expanded into micrometre scales, their geometry can be decided by smaller scale DNA origami junctions.…”
Section: From Biomoleculesmentioning
confidence: 99%
“…One of the typical successful examples would be DNA nanotechnology such as DNA origami in which various structures can be logically nanoarchitected through specific baseparing and programmed DNA sequences [200][201][202]. Schulman and co-workers demonstrated hierarchic self-assembly of DNA nanotubes in micrometre scale from DNA strands with programmed sequences [203]. Even though the assembled structures expanded into micrometre scales, their geometry can be decided by smaller scale DNA origami junctions.…”
Section: From Biomoleculesmentioning
confidence: 99%
“…190 They also affected the properties of the nal composite, 191 especially mechanical properties. Uniform dispersion of carbon nanotubes within a DNA matrix can be achieved, 192 and their complexes have been found to enable separation of carbon nanotubes 190,193 as well as preparation of composites and bers [194][195][196] and nanometer-scale electronic (nanoelectronic) devices. 197,198 An in-depth review of the science and technology of carbon nanotube-DNA composite materials and related applications is available in the literature.…”
Section: Strongly Coupled Carbon Nanotube-polymer Systemsmentioning
confidence: 99%
“…DNA cages refer to wireframe architectures assembly from DNA strands (Chen and Seeman, 1991;Wang et al, 2019). Various DNA cages include DNA polyhedrons (Wang et al, 2019) and DNA nanotube (Jorgenson et al, 2017;Mohammed et al, 2017) were reported. DNA polyhedrons represent a 3D cage-like compact structure which is stable and easily absorbed by cells.…”
Section: Wireframe Dna Cagesmentioning
confidence: 99%
“…DNA polyhedrons represent a 3D cage-like compact structure which is stable and easily absorbed by cells. Due to structural closure, they are compact, mechanically strong, size-tunable and noncytotoxic (Jorgenson et al, 2017;Mohammed et al, 2017). Among them, DNA tetrahedron is the most commonly seen one (He et al, 2008;Liang et al, 2014), as demonstrated in Figure 1.…”
Section: Wireframe Dna Cagesmentioning
confidence: 99%